2012
DOI: 10.1088/0004-637x/756/1/19
|View full text |Cite
|
Sign up to set email alerts
|

SEISMIC EVIDENCE FOR A RAPIDLY ROTATING CORE IN A LOWER-GIANT-BRANCH STAR OBSERVED WITHKEPLER

Abstract: -Rotation is expected to have an important influence on the structure and the evolution of stars. However, the mechanisms of angular momentum transport in stars remain theoretically uncertain and very complex to take into account in stellar models. To achieve a better understanding of these processes, we desperately need observational constraints on the internal rotation of stars, which until very recently were restricted to the Sun. In this paper, we report the detection of mixed modes -i.e. modes that behave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
498
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 366 publications
(538 citation statements)
references
References 89 publications
(117 reference statements)
38
498
1
1
Order By: Relevance
“…Previous analyses (Beck et al 2012;Deheuvels et al 2012;Mosser et al 2012a) only revealed the ratio of the (Mosser et al 2011b) for = 0, 1, 2 and 3 and are indicated with blue, red, green and yellow vertical bars, respectively. The effects of rotation are visible as the splitting of dipole modes, located in the centre of each panel.…”
Section: Testing Of the Rotational Profile From Forward Modellingmentioning
confidence: 99%
“…Previous analyses (Beck et al 2012;Deheuvels et al 2012;Mosser et al 2012a) only revealed the ratio of the (Mosser et al 2011b) for = 0, 1, 2 and 3 and are indicated with blue, red, green and yellow vertical bars, respectively. The effects of rotation are visible as the splitting of dipole modes, located in the centre of each panel.…”
Section: Testing Of the Rotational Profile From Forward Modellingmentioning
confidence: 99%
“…In the last few years, we have begun to observe with asteroseismology the internal radial rotation profiles of stars from hydrogen-burning main-sequence phases Pápics et al 2015;Saio et al 2015;Schmid et al 2015;Triana et al 2015), through to subgiant and red giant phases (Beck et al 2012;Mosser et al 2012;Deheuvels et al 2012Deheuvels et al , 2014Deheuvels et al , 2015, and even on to the late evolutionary stages of subdwarf B stars (Van Grootel et al 2009) and white dwarfs ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional invaluable information about the evolution of stars is provided by the study of the internal structure of red giants Beck et al 2011Beck et al , 2012Mosser et al 2012a,b) and of sub-giants (Deheuvels et al 2012;Benomar et al 2013). The large asteroseismic database of Kepler allowed us to estimate the properties of an ensemble of solar-type stars that is large enough to perform statistical studies .…”
Section: Introductionmentioning
confidence: 99%